2nd AIR SCADRON STRATEGY INCREASING SUPPORT OF AIR DEFENSE OPERATIONS THROUGH WEATHER MODIFICATION TECHNOLOGY - Fitrianto Ali Ngimron; TS Lumban Toruan; Dohar Sianturi (Strategi Pertahanan Udara, 2022)
The involvement of the Indonesian Air Force in Weather Modification Technology Operations is part of Military Operations Other than War. Along with the rapid development of technology in the field of Weather Modification which makes the use of this technology easier. One of the benefits of Operation Weather Modification Technology is to support Air Defense Operations. However, in several implementations there are several obstacles encountered, the Air Squadron is not yet equipped with a sophisticated weather radar. Today's weather radar requires a technology upgrade. The 2nd Air Squadron had problems carrying out TMC Operations at night. In order for the use of Weather Modification Technology to be used optimally for military operations and able to support air defense operations, an effective and efficient strategy is needed. The purpose of this study is to analyze the main obstacles, the implementation of Air Defense Operations, possible air threats and strategies to increase support for air defense operations through the use of Weather Modification Technology by the Air Squadron 2. The research method used is a qualitative case study design. Theories used include strategy, air power, weather manipulation and air defense operations. The results of this study are the main obstacles encountered related to the use of Air Squadron TMC are weather conditions, lack of raw materials and inadequate equipment. The conditions for the implementation of air defense operations are not optimal and there are several threats that can arise in the Indonesian air sovereignty area. The strategy used to achieve the goal is to overcome existing obstacles and improve the ability of the Air Squadron 2 through existing instruments. The conclusion of this study is that threats to air sovereignty can be anticipated by optimizing the Air Squadron 2's weather modification capabilities.Keywords : 2nd Air Squadron Ability, Air Defense Operations, Utilization, Strategy, Weather Modification Technology